Tafsir Saintifik dalam Penafsiran Al-Qur’an: Analisis Kritis atas Epistemologi dan Metodologinya - Isnan Ansory; Muhammad Nur Kholis (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
Qur’anic studies that seeks to correlate cosmological verses (āyāt kauniyyah) with modern scientific discoveries. The study aims to clarify the nature of scientific exegesis, trace its historical development and key figures, and analyze the methodological, epistemological, theological, and contextual critiques directed at this approach. Employing a qualitative library research method, the study utilizes descriptive-analytical, critical-comparative, and hermeneutic-philosophical analyses of scientific tafsir works and their critiques. The findings indicate that scientific exegesis contributes positively to fostering dialogue between revelation and science and to strengthening faith through reflection on natural phenomena. Nevertheless, this approach entails significant methodological risks when scientific theories—being empirical and provisional—are treated as foundational interpretive frameworks. Therefore, the article emphasizes the necessity of a balanced approach that positions science as a reflective and complementary tool rather than a determinant of revelatory truth, thereby preserving the theological authority and spiritual depth of the Qur’an